Comparison of spirometric parameters in athletes engaged in aerobic and anaerobic sports: a cross-sectional study - Rajaure, Y. S.; Thapa, B.; Budhathoki, L.; Rana, S. R.; Khadka, M. (Annals of Medicine & Surgery, 2023)
Background: Pulmonary function tests are better among athletes than non-athletes. The spirometry parameters may vary among athletes involved in aerobic and anaerobic sports. This study aims to study the difference in spirometry parameters among aerobic and anaerobic sports athletes.